Manajemen Bandwidth Melalui IP Filter Mikroktik HAP Lite Di FT Uniska - Novi Ari Saputro (Jurnal JEETech, 2022)
Bandwidth management for clients connected to the internet network is needed in the upload and download process. In this study used additional devices in the form of a mikrotik router and research sites at the Faculty of Engineering UNISKA, Kediri. The study discusses Quality of Service (QoS) with 4 indicators, namely throughput, packet loss, delay, and jitter. The results showed that the speedtest application bandwidth did not exceed the specified limit. And in the wireshark application, it is shown that the calculation of QoS throughput for each user is not more than 100 Kbps, then the standard parameters according to TIPHON are categorized as "BAD" with an index of "0". In the QoS packet loss, each user gets a value of 0, then the standard parameters according to TIPHON are categorized as "PERFECT" with the index "4". In the QoS delay, each user gets a value less than 100 s, then the standard parameters according to TIPHON are categorized as "PERFECT" with the index "4". And on the QoS jitter of each user, the value is below the number 1, then the standard parameters according to TIPHON are categorized as "GOOD" with an index of "3".